Contemporary auditing : for students - Gupta, Kamal (New Delhi, India : Tata McGraw-Hill, 1992)
This new edition incorporates the latest professional pronouncements, legislative changes and other relevant developments that have taken place since the publication of the third edition
includes index
ijb, 17/10/2018
Loans